Pengaruh Investment Opportunity Set, Political Connection dan Gender Diversity terhadap Kualitas Laba dengan Moderasi Kepemilikan Institusional - Widya Ayu Lestari; Dirvi Surya Abbas; Imam Hidayat (Politeknik Ganesha Medan, 2025)
This study aims to determine the effect of investment opportunity set, political connection and gender diversity on earnings quality with moderating variables of institutional ownership in manufacturing companies listed on the Indonesia Stock Exchange (IDX). The research period used is 5 years, namely the 2020-2024 period. The population of this study includes all manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2024 This research uses Eviews version 12. Sampling using purposive sampling technique using criteria to retrieve data. The results showed that: 1). Investment opportunity set has no effect on earnings quality; 2). Political connection has no effect on earnings quality; 3). Gender diversity has a significant negative effect on earnings quality; 4) Institutional ownership cannot strengthen or weaken the investment opportunity set and political connection on earnings quality; 5) Institutional ownership can weaken gender diversity on earnings quality.